1997
DOI: 10.1111/j.1651-2227.1997.tb08605.x
|View full text |Cite
|
Sign up to set email alerts
|

IGF‐I, IGF‐II, free IGF‐I and IGFBP‐1, ‐2 and ‐3 levels in venous cord blood: relationship to birthweight, length and gestational age in healthy newborns

Abstract: The insulin‐like growth factors (IGF‐I and IGF‐II) and their binding proteins (IGFBPs) have been implicated in regulating fetal growth and development. The aim of this study was to determine whether fetal IGFs correlate with auxologic data at birth and/or gestational age. Venous cord blood was obtained from 138 healthy newborns immediately after birth and clinical data were recorded using a standardized data sheet. For the determination of IGF‐I and IGF‐II, IGFBP‐blocked radioimmunoassays were used. A coated‐t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(37 citation statements)
references
References 37 publications
4
33
0
Order By: Relevance
“…Most studies addressing the associations of the IGF system with birth size have focused on differences between small for gestational age neonates resulting from a variety of etiologies and appropriate for gestational age neonates; however, the greatest breast cancer risks are observed for women born heavy. In studies conducted in normal pregnancies with a range of birth weights, the positive association between birth size and cord IGF-I concentrations is well established (89)(90)(91)(92)(93)(94)(95)(96)(97)(98). IGFBP-3 has also been positively associated with birth size in most studies (75,95,96,99), whereas IGFBP-1 may be inversely associated (90,95).…”
Section: Prominent Hypotheses To Explain Prenatal Risk Factorsmentioning
confidence: 98%
See 1 more Smart Citation
“…Most studies addressing the associations of the IGF system with birth size have focused on differences between small for gestational age neonates resulting from a variety of etiologies and appropriate for gestational age neonates; however, the greatest breast cancer risks are observed for women born heavy. In studies conducted in normal pregnancies with a range of birth weights, the positive association between birth size and cord IGF-I concentrations is well established (89)(90)(91)(92)(93)(94)(95)(96)(97)(98). IGFBP-3 has also been positively associated with birth size in most studies (75,95,96,99), whereas IGFBP-1 may be inversely associated (90,95).…”
Section: Prominent Hypotheses To Explain Prenatal Risk Factorsmentioning
confidence: 98%
“…IGFBP-3 has also been positively associated with birth size in most studies (75,95,96,99), whereas IGFBP-1 may be inversely associated (90,95). Associations of IGF-2 with birth size are unclear (92,93,99), as is the role of IGFBP-2, the main IGFBP in the fetal circulation (99). In contrast, birth weight is generally not associated with concentrations of IGF-I (100, 101), IGFBP-1 (100-102), or IGFBP-3 in the maternal circulation (103).…”
Section: Prominent Hypotheses To Explain Prenatal Risk Factorsmentioning
confidence: 99%
“…Previous studies have shown that IGF-I has a more critical role than the other factors (56)(57)(58), and growth hormone is not an important regulator of IGF-I secretion during perinatal life (57,58). In addition, children with IGF-I gene deletion are characterized by severe prenatal and postnatal growth retardation (59).…”
Section: Insulin-like Growth Factor-i (Igf-i)mentioning
confidence: 99%
“…weight is positively correlated with cord blood IGF1 levels (Osorio et al 1996, Klauwer et al 1997, and so levels are low in small-for-gestational-age (SGA) infants and are enhanced in large-for-gestational-age babies (Table 1). Evidence for the importance of IGF2 in this regard comes from the observation that the IGF2 gene is maternally imprinted (Giannoukakis et al 1993).…”
Section: Influence Of Maternal Growth Factors On Fetal Growthmentioning
confidence: 99%